Influence of the cooling system on dairy cattle productivity in the Huaura valley, Peru - Vásquez Requena, Ángel Gerardo (2017)
The influence of a cooling system (continuous ventilation and intermittent water spray) on productive, reproductive and economic levels of dairy cattle during the summer of 2012 was compared to previous summers where cooling systems were not present. Records of 890 cows in production of two dairies of the Valley Huaura, Lima, Peru were analyzed. Milk production, total solids, conception rate, services per conception and cost-effective data was collected. Farm 2 achieved a significant increase in milk production (p<0.05) due to the cooling system, while in Farm 1 was observed an increase in the percentage of total solids and a reduction in conception rate (p<0.05). The results showed that the use of a cooling system (fans and sprinklers) to reduce heat stress in dairy cows can be effective depending on the circumstances of each dairy herd.